Franco's justice repression in Madrid after the Spanish Civil War - Ruiz, Julius, 1973- (Oxford historical monographs., 2005)
Using extensive but only recently available judicial records, this work examines the consequences in Madrid of General Franco's victory in the Spanish Civil War.